Potential use of biaromatic L-phenylalanyl derivatives as therapeutic agents in the treatment of sickle cell disease. - Votano, J R (1984)
N-Phenylacetyl-L-phenylalanine (PAP) and L-phenylalanyl-3-aminopyridine ( PAPA ) are biaromatic agents with properties that make them suitable candidates for the development of a useful therapeutic agent for the treatment of sickle cell disease. PAP and PAPA are taken up by the erythrocyte to give intra-/extracellular concentration ratios of 2.2 and 1.5, respectively, after a 2-hr exposure period. The intracellular buildup of PAP and PAPA produces moderate decreases in the mean corpuscular hemoglobin concentration (MCHC) of 6 and 10%, respectively, at 3 mM and a further decline in MCHC with increased concentration. Both PAP and PAPA increase the deoxy-Hb S solubility, CS. If the solubility in the absence of the agent is COS, PAP and PAPA have CS/COS values of 1.21 and 1.14 at 20 mM, respectively, compared with a value of 1.06 for L-phenylalanine itself. Filterability assays of partially dexygenated homozygous sickle cells shows an increase in cell flexibility of 7 to 16 times more than that of untreated cells when these agents are present at 3-6 mM. These results are largely due to the reduction in the Hb S polymer content of the treated cells. At 3 mM or less, both PAP and PAPA delay the onset of gelation in reversible sickle cells for time periods that are likely to be therapeutically useful.